Prognostic relevance of rosette-like features in osteosarcoma. Issue 11 (4th November 2003) - Okada, K; Hasegawa, T; Yokoyama, R; Beppu, Y; Itoi, E
Abstract : Aims: To clarify the prognostic relevance of rosette-like features and other clinicopathological and immunohistochemical variables in patients with osteosarcoma. Methods: Clinicopathological and immunohistochemical variables were analysed in 131 patients with non-metastatic high grade conventional osteosarcoma, with particular attention to the prognostic impact of rosette-like features. Results: Rosette-like features were present in 18 (14%) cases. Rosette-like features were significantly associated with the osteoblastic subtype, numerous osteoclast-like giant cells, moderate pleomorphism, frequent haemangiopericytoma-like vascular patterns, epithelioid cytological features, positive immunoreactivity for epithelial membrane antigen and CD56, and negative staining for cytokeratin. In a multivariate analysis, rosette-like features (relative risk (RR), 3.8), a poor chemotherapy effect (RR, 2.9), and a tumour size of 10 cm or more (RR, 2.8) were identified as unfavourable prognostic factors. Conclusions: Rosette-like features can easily be identified from routine histological slides and the relative risk in patients with non-metastatic, conventional osteosarcoma is as high as other well known prognostic factors, including large size and poor chemotherapy effect.